Effects of Sweetened Beverage Consumption on Dental Caries and Oral Health Related Quality of Life in Children - Syeda Nadia Firdous , Nirmal Bilal,Safura Idrees ,Awab Aali Ahmad , Ramsha Naveed,Aareez Ali Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Dental caries is a crucial public wellbeing concern between children, with sugar-sweetenedbeverage consumption identified a serious risk factor. Objective: This research aim to assessfrequencyandthe effect of sugarcontaining beverage consumption on dental cavities and oral cavity and health-related quality of life in children